Strategi Guru dalam Mengatasi Kesulitan Membaca Permulaan pada Siswa Kelas 1 SD: Teacher Strategies in Overcoming Beginning Reading Difficulties in Grade 1 Elementary School Students - Ersa Ersa Winny; Haifaturrahmah Haifaturrahmah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Early reading difficulties are a fundamental issue that impacts the readiness and development of basic literacy in elementary school students, particularly in grade one. Students' inability to master early reading skills can hinder their achievement of competencies in subsequent learning stages. This study aims to examine in depth the various learning strategies teachers implement to overcome early reading barriers using a Systematic Literature Review (SLR) approach. The study was conducted by searching for scientific articles published between 2015 and 2025 obtained from Google Scholar, DOAJ, and Scopus databases. Source selection was based on strict inclusion criteria and followed the PRISMA selection process to ensure data accuracy and reliability. The analysis results indicate that effective learning strategies include the systematic application of phonics methods, the use of multisensory media such as letter cards, pictures, and flannel, the provision of individual guidance for students experiencing specific difficulties and strengthening collaboration between teachers and parents to support the learning process at home. These findings emphasize the importance of adaptive, diagnostic, and sustainable learning strategies in overcoming early reading difficulties. This study recommends developing interactive technology-based learning models and increasing synergy between schools and parents to strengthen early literacy skills in a sustainable manner.